Functionalised polyhedral oligomeric silsesquioxane with encapsulated fluoride – first observation of fluxional Si⋯F interactions in POSS. Issue 1 (20th November 2020) - Laird, Mathilde; Totée, Cédric; Gaveau, Philippe; Silly, Gilles; Van der Lee, Arie; Carcel, Carole; Unno, Masafumi; Bartlett, John R.; Wong Chi Man, Michel
Abstract : The first observation of fluxional covalent Si⋯F interactions in functionalised T8 -F cage silsesquioxanes containing an encapsulated fluoride is reported. Abstract : The synthesis of a styryl functionalised POSS incorporating an encapsulated fluoride ion within a (SiO1.5 )8 cage (T8 -F) is reported. It was characterised by single crystal XRD, MALDI-MS, FTIR, solution ( 29 Si, 19 F, 13 C, 1 H) and solid state ( 29 Si, 19 F) NMR. In the absence of 1 H decoupling, the 29 Si solution NMR spectrum exhibited a triplet of doublets. In contrast, 1 H, 19 F and 1 H/ 19 F double-decoupling resulted in two, three and one signal, respectively, being consistent with a single Si site whose 29 Si NMR signal is modulated by both the proximal aromatic-ring protons and fluoride. The associated Si⋯F coupling constant (2.5 Hz) is substantially lower than expected for a covalent Si–F bond and arises from a fluxional Si⋯F covalent effect in which the F − interacts equivalently with all eight Si atoms. Additional variable temperature NMR studies demonstrated a threshold at −5 °C below which no Si⋯F interactions are observed, and above which an increasing Si⋯F covalent character occurs.